Self‐Delivering Nanodrugs Developed via Small‐Molecule‐Directed Assembly and Macrophage Cloaking for Sonodynamic‐Augmented Immunotherapy. Issue 16 (22nd May 2022) - Xie, Fang; Liu, Zongjunlin; Wang, Peiyuan; Cai, Meimei; Li, Yang; Yan, Jianghua; Lin, Qin; Luo, Fanghong
Abstract: The self‐delivery of sonosensitizers and immunomodulators to tumor areas, which is highly recommended for enhancing sonodynamic immunotherapy, remains a challenge. Herein, a self‐delivering nanodrug (HB‐NLG8189, drug loading: ≈100 wt%) is developed by the small‐molecule self‐assembly of "HB" (a new clinical photosensitizer) and NLG8189 (indoleamine‐(2, 3)‐dioxygenase (IDO) pathway inhibitor) for sonodynamic‐augmented immunotherapy; this preparation method ensures the absence of excipient‐related toxicity and immunogenicity. To evade immune recognition and prolong the circulation time, the HB‐NLG8189 nanodrugs are camouflaged using macrophage cell membranes (MPCMs). The constructed HB‐NLG8189@MPCM nanodrugs show an ability to preferentially accumulate within tumors. Upon ultrasound triggering, the HB‐NLG8189@MPCM is able to generate reactive oxygen species efficiently for robust sonodynamic therapy; it induces immunogenic cell death, initiates an antitumor immune response to activate tumor‐specific effector T cells, and promotes the secretion of inflammatory cytokines. The concomitant delivery of NLG8189 reverses the immunosuppressive tumor microenvironment by restraining IDO‐1 activation and the intratumoral infiltration of regulatory T cells. Sonodynamic‐augmented immunotherapy with HB‐NLG8189@MPCM significantly inhibits the growth of both primary and distant tumors with little systemic toxicity. The biomimetic self‐delivery nanodrug provides a promising paradigm for improving sonodynamic immunotherapy. Abstract : A novel carrier‐free nanodrug camouflaged by a macrophage membrane, which is developed by small‐molecule self‐assembly of "HB" (a new clinical photosensitizer) and NLG8189 (IDO pathway inhibitor) for sonodynamic‐augmented immunotherapy, can reverse the immunosuppressive tumor microenvironment and promote the intratumor infiltration of T cells to inhibit the growth of both primary and distant tumors, while avoiding the excipients‐related toxicity and immunogenicity.